DEVELOPMENT OF ASSEMBLY LINE AND OPERATORASSIGNMENT MODELS CONSIDERING OPERATOR SKILL LEVEL DIFFERENCE IN THE TAILBOOM OF HELICOPTER MK-II ASSEMBLYLINE - Agus Dinar, Budi
The assembly line in Tailboom of Helicopter MK-II currently uses the fixed layout concept with 1 wrk station and serialized. A stage has 3 different operation types to process it, there are mechanical installation,sealant, and inspection. Especially for mechanical installation,provide operator with 2 level skills, that is mechanical installer skilled (MIS) and mechanical installer unskilled (MIU) with difference workmanship on each process. In 2019, PT.X has production target 22 units of tailboom (18 units in 2019 + 4 units in 2018 deficiency). Based on calculations, the takt time value of fulfillmentper unit of tailboom is 91 hours, whereas the actual length of time for 3 large components,pylon, cone, junction require 133,153,123 hours each,with default formation,10 operators (4 MIS, 2 MIU, 2 Sealant operators, 2 Inspector). A cross-assembly model is necessarydesigned to be able to regulate the assignment of operators who at the same time can balance workload to meet the target of cycle time. The proposed model isMixed Integer Linear Programming (MILP) analytic model. This model has an objective functioncycle time minimization, with input in the form of operating data, operator data and precedence diagrams.While the output in the form of work stations that are formed, the placement of operations at work stations,assigning operators to operations, cycle time values of stations formed. To fitwith the actual conditions, in this study it is necessary to make some model adjustment, first, by modifying the precedence diagram by adding a dummy task toaccommodate each actual operation that requires 2 operators, only the type of operationmechanical installation that requires 2 operators. Second, to accommodate the ruleswhich is applied by the customer, for each operation that requires 1 operator, is assignedmust be a skilled operator, and for operations that require 2 operators, must be assignedat least 1 skilled operator. In an effort to achieve the production target of 22 tailboom units / year, the solution from computational process of the proposed model produces a cross-assembly with 2 work stations. The proposed model is capable to decrease the cycle time of each component of the pylon: 133 hours to 71 hours,cone: 153 hours to 82 hours, and junction: 123 hours to 71 hours with default formation.In addition, this study also proposes 2 proposed formations with a total of 8 operators. Formationproposal 1, with a reduction of 2 MIS operators, resulting in a cycle time that is still belowtakt time value but the most efficient for the cost salary of all mechanical installer operatorsin producing 22 units of tailboom. As for the formation of proposal 2, with a reduction of 2MIU operator, is able to produce the smallest cycle time value in total production 22 units of pylon, cone, junction.